Case Report: Anti-TNF Treatment Failure in a Patient With Immune Checkpoint Inhibitor-Induced Severe Colitis - Fang, Leilei; Liu, Changqin; Sun, Xiaomin; Liu, Zhanju (Frontiers in Oncology, 2022)
Immune checkpoint inhibitor (ICI)-induced colitis is one of known complications of therapies targeting cytotoxic programmed cell death protein 1 (PD-1), T lymphocyte-associated antigen 4 (CTLA-4) and programmed cell death ligand 1 (PD-L1). ICI-associated colitis is routinely treated with immunosuppressive therapy, including corticosteroids and/or agents targeting tumor necrosis factor-α (TNF-α). In this report, a 69-year-old male patient developed severe ICI-induced colitis in two weeks after anti-PD-L1 mAb (i.e., durvalumab) treatment and unexpectedly failed to respond to systemic corticosteroid, anti-TNF and anti-integrin agents, and unfortunately died in one month. This case reminds clinical physicians to be on the alert for early onset acute ICI-induced colitis and emphasizes that urgent optimized rescue measures are requied for patients with severe ICI-induced colitis.